1987
DOI: 10.1021/ac00129a023
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic micronebulizer inferface for high-performance liquid chromatography with flame photometric detector

Abstract: An ultrasonic micronebulizer Interface for effective nebullzation at 2-20 juL/mln liquid was developed to allow the determination of nonvolatile analytes by microbore HPLC with virtually unmodified gas chromatographic detectors. A detectability of 50 pg/s phosphorus was obtained with a dynamic range of 3 decades and acceptable peak broadening using a flame photometric detector (FPD) as a detector. Solvent compatibility appears mainly determined by the choice of chromatographic detector. Dual-wavelength operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Further, acetonitrile significantly increases the background noise and quenches the detector signal at even low percentages. Various interface designs have been proposed to overcome these problems [201][202][203][204][205]. Kientz and Brinkman [18] recently summarized and discussed the advantages and limitations of the use of flame photometric detection in microcolumn LC.…”
Section: Flame Photometric Detectionmentioning
confidence: 99%
“…Further, acetonitrile significantly increases the background noise and quenches the detector signal at even low percentages. Various interface designs have been proposed to overcome these problems [201][202][203][204][205]. Kientz and Brinkman [18] recently summarized and discussed the advantages and limitations of the use of flame photometric detection in microcolumn LC.…”
Section: Flame Photometric Detectionmentioning
confidence: 99%
“…It has been reported that ultrasonic nebulizers are capable of operating at flow rates down to 20 mL min À1 , without the need for any makeup solvent. 21,22 The ability to provide very high transport efficiency at flow rates in the range of 2-20 mL min À1 suggests good potential for ultrasonic micronebulizers use with microwave induced plasma spectrometry. Ultrasonic nebulizers are popular with inductively coupled plasma (ICP) optical emission (OES) and mass spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ultrasonic nebulizers are capable of operating at flow rates down to 20 mL min À1 , without the need for any makeup solvent. 17,18 The ability to provide very high transport efficiency at flow rates in the range of 2-20 mL min À1 suggests good potential for ultrasonic micronebulizers use with plasma spectrometry. Ultrasonic nebulizers become popular with inductively coupled plasma (ICP) optical emission (OES) and mass spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%